Expression of CD94 and 56(bright) on natural killer lymphocytes - the influence of exercise - Horn, P L; Leeman, K; Pyne, D B; Gore, C J (International journal of sports medicine, 2002)
This study was undertaken to determine the effects of acute intense exercise on the cell membrane-bound glycoprotein designated cluster of differentiation (CD) 94. This marker on natural killer (NK) lymphocytes contributes to control of cell function. CD94 was measured on natural killer lymphocytes from 11 adult (average 25 yrs), well-trained male subjects, (Vdot;O 2 peak mean, 5.01 L x min -1) before and immediately after a final, 4 min all-out, cycle ergometry test. Using flow cytometry, lymphocyte populations were distinguished as either having (CD94 +) or lacking (CD94 -) the cell marker. The absolute number of CD94 + and CD94 - natural killer cells increased with exercise but the mean fluorescence intensity (MFI) for CD94 decreased from pre 131, to post 117 (p = 0.01). The percentage of NK cells that were CD94 + did not change, but exercise did mobilise natural killer cells of greater MFI for the surface markers designated CD16/CD56 (pre 750 to post 1 050, p < 0.001). The latter suggests that some exercise-mobilised natural killer cells may have originated from the liver as CD56 +bright cells.